2023
DOI: 10.1038/s41598-023-38434-w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress increases in liver of lactating rats after BPF-low-dose exposure: perinatal effects in the offspring

Abstract: Bisphenol F (BPF) is replacing Bisphenol A (BPA) in the manufacture of products due to endocrine-disrupting effects. BPF monomers can also be released into the environment and enter the food chain, resulting in human exposure to low doses. Since bisphenols are primarily metabolized by the liver, this organ is more vulnerable to lower doses of bisphenols than others. Exposure during prenatal development may increase the risk of diseases in adulthood. The aim was to evaluate whether BPF administration could gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Our results in PND6 offspring showed an increase in gene and protein expression of iNOS and no change in the eNOS isoform in both males and females, as well as an increase in inducible mRNA and protein HO-1d levels in both sexes. In a previous study [ 16 ], higher levels of the GSSG/GSH ratio were found in females than in males, but antioxidant enzymes were decreased in both sexes.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our results in PND6 offspring showed an increase in gene and protein expression of iNOS and no change in the eNOS isoform in both males and females, as well as an increase in inducible mRNA and protein HO-1d levels in both sexes. In a previous study [ 16 ], higher levels of the GSSG/GSH ratio were found in females than in males, but antioxidant enzymes were decreased in both sexes.…”
Section: Discussionmentioning
confidence: 89%
“…In a previous study by our research group, antioxidant enzyme activities were decreased, and oxidized glutathione levels were increased after low doses of BPF in lactating Long Evans rats and their offspring, in addition to increased lipid peroxidation. Thus, LBPF increases oxidative stress [ 16 ]. However, it was unknown whether BPF could increase nitrosative stress and serve as a stimulus to trigger inflammatory responses after administration of two doses of BPF: a low dose of 0.0365 mg/kg/b.w./day (LBPF) and a high dose of 3.6 mg/kg/b.w./day (HBPF) in the liver of lactating dams and PND6 offspring after pre- and perinatal BPF exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In females, the antioxidant properties of estrogen play a significant role in influencing the expression and Furthermore, induction of inflammations and oxidative damage were also linked to exposure to BPA alternatives. Both of these are well demonstrated in promoting impaired fetal development and contributing to various adverse outcomes in offspring [36,39,[45][46][47]. Lastly, modulations in immune system responses have been reported after exposure to BPA alternatives during gestation and lactation periods.…”
Section: Potential Mechanisms Of Sex-specific Effectsmentioning
confidence: 98%
“…Structural similarity to BPA has put BPF under surveillance for its toxicity. For example, zebrafish chronic exposure to BPF resulted in hepatic fibrosis and steatosis, even at environmentally relevant concentrations [9] and more noteworthy, perinatal exposure to low-dose BPF contributed to hepatic oxidative stress in the offspring rats [10] . Our recent study further demonstrated the roles of oxidative stress in promoting lipid deposition in hepatic cells, as evidenced by the mitigation of mitochondrial ROS resulting in the inhibition of lipid droplet deposition [11] .…”
Section: Introductionmentioning
confidence: 99%